Developing a dynamic virtual stimulation protocol to induce linear egomotion during orthostatic posture control test - Da-Silva,Paulo José Guimarães (2016)
Abstract Introduction In this work, the effect of a dynamic visual stimulation (DS) protocol was used to induce egomotion, the center of pressure (COP) displacement response. Methods DS was developed concerning the scenario structure (chessboard-pattern floor and furniture) and luminance. To move the scenario in a discrete forward (or backward) direction, the furniture is expanded (or reduced) and the black and white background is reversed during floor translation while the luminance is increased (or reduced) by steps of 2 cd/m2. This protocol was evaluated using COP signals from 29 healthy volunteers: standing on a force platform observing the virtual scene (1.72 × 1.16 m) projected 1 m ahead (visual incidence angle: θl = 81.4° and θv = 60.2°), which moves with constant velocity (2 m/s) during 250 ms. A set of 100 DS was applied in random order, interspersed by a 10 s of static scene. Results The Tukey post-hoc test (p < 0.001) indicated egomotion in the same direction of DS. COP displacement increased over stimulation (8.4 ± 1.7 to 22.6 ±5.3 mm), as well as time to recover stability (4.1 ± 0.4 to 7.2 ± 0.6 s). The peak of egomotion during DSF occurred 200 ms after DSB (Wilcoxon, p = 0.002). Conclusion The dynamic configuration of this protocol establishes virtual flow effects of linear egomotion dependent on the direction of the dynamic visual stimulation. This finding indicates the potential application of the proposed virtual dynamic stimulation protocol to investigate the cortical visual evoked response in postural control studies.